Foreign capital in Russia: Taking stock after two years of war - Vasily Astrov (The Vienna Institute for International Economic Studies (wiiw), 2024)
Unlike most other countries of Central, East and Southeast Europe, even prior to the war Russia's economic model was not really based on attracting foreign direct investment. On top of that, many of the Western firms announced plans to withdraw following the country's invasion of Ukraine in February 2022. However, two years after the war began, only 9.5% of foreign companies have fully exited Russia, while another 32.2% have curtailed their Russian operations. The exodus of foreign capital has slowed markedly over time, to a large degree due to the progressive tightening of the regulatory hurdles for exit. In general, foreign companies that have stayed find themselves between a rock and a hard place. On the one hand, the regulatory hurdles, the unfavourable exit terms and the non-negligible risk of nationalisation make exit a difficult, costly and potentially risky move; on the other hand, the decision to stay is fraught with risks of its own.
Keywords: F21; F23; 330; foreign direct investments; regulatory hurdles for business exit